STUDENTS’ WRITING ANXIETY AND ITS CORRELATION WITH WRITING PERFORMANCE - Dela Masita Fitrinada; Bambang A Loeneto; Fiftinova Fiftinova (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2018)
Abstract: The present study was aimed at investigating the correlation between students’ writing anxiety and their writing achievement. Eighty five EFL students of English Education Study Program of FKIP at Sriwijaya University in academic year 2016/2017 were selected by using purposive sampling. The study used a quantitative research method of correlational design. The data were collected by distributing writing anxiety questionnaire and a writing test which were analyzed statistically. The results of correlational analysis showed that a fair negative significant correlation between students’ writing anxiety and their writing achievement with r obtained = -.545 and p-value -.000. Another finding from this study showed that a significant correlation between each aspect of writing anxiety to writing achievement (somatic anxiety was -.000, avoidance behaviour was -.000, and cognitive anxiey was -.000). Lastly, the contribution of writing anxiety on students’ writing achievement was .297, and it indicated that students’ writing anxiety gave significant effect in the level of 29.7% toward writing achievement. Keywords: Anxiety, Writing Anxiety, writing ahievement, Correlation.